Influence of Carotid Intima Media Thickness on The Patient's Memory Function Fails Heart with Ejection Fraction Left Ventricle Descends - Tongku, Aurelia Sartika; Pertiwi, Junita Maja; Tangkudung, Gilbert; Kembuan, Mieke A.H.N.; Momole, Ansye G.N. (Eduvest - Journal of Universal Studies, 2025)
Heart failure (HF) with reduced left ventricular ejection fraction (LVEF) is frequently associated with cognitive decline, including memory impairment. This study investigates the relationship between carotid intima-media thickness (CIMT), a marker of subclinical atherosclerosis, and specific memory domains immediate, recall, and recognition in patients with reduced LVEF. A cross-sectional study was conducted on 52 HF patients at Prof. Dr. R.D. Kandou Hospital. Memory function was assessed using the Word List Memory Test, and CIMT was measured via carotid ultrasound. Regression analysis showed that increased CIMT in the left common carotid artery (CCA Sinistra) was significantly associated with lower immediate and recognition memory performance. Furthermore, elevated CIMT in both carotid arteries was negatively correlated with recall memory. These findings highlight a potential vascular contribution to cognitive impairment in HF patients, suggesting that subclinical carotid atherosclerosis may impair cerebral perfusion. The study provides clinical insight into the importance of vascular assessment in managing cognitive health in HF populations. Early detection of carotid pathology may offer a strategy to prevent or reduce cognitive decline in these patients.